Sublethal effects of mercury on growth and biochemical com position and their recovery in Oreochromis mossambicus - Khanee, KMA Nazeemul; James, R; Sivakumar, V; Muthuramalakshmi, M (Indian Journal of Fisheries, 2011)
The median lethal concentration of mercury for 96 hr was 0.06 ppm for the fish Oreochromismossambicus. Test animals \ ere exposed to sublethal concentrations of mercury (0.01 and 0.02 ppm) for4 weeks (exposure period). They were transferred to metal impoverished water for another 4 weeks(recovery period). The growth of the test animals was estimated weekly throughout the experimentalperiod. Protein, carbohydrate and lipid contents were also estimated in tissues of muscles, liver and gill.Significant reduction of growth and biochemical components was observed during exposure period andthe loss was regained up to certain extent during recovery period.